Real‐Time PCR and Droplet Digital PCR: two techniques for detection of the JAK2V617F mutation in Philadelphia‐negative chronic myeloproliferative neoplasms. (20th July 2015) - Fontanelli, G.; Baratè, C.; Ciabatti, E.; Guerrini, F.; Grassi, S.; Del Re, M.; Morganti, R.; Petrini, I.; Arici, R.; Barsotti, S.; Metelli, M. R.; Danesi, R.; et al.
Summary: Introduction: Philadelphia‐negative chronic myeloproliferative neoplasms (MPNs) are clonal disorders that present JAK2 V617F mutation in 50–95% of cases. The main objective of this study was the comparison of two PCR methods, real‐time (qPCR) and droplet digital PCR (DD‐PCR) for detection of the JAK2 V617F mutation, to assess analytic sensitivity, specificity, and feasibility of the two methods. Methods: Ninety‐nine patients with MPN of 225 presenting the JAK2 V617F mutation by qPCR have been evaluated by DD‐PCR also. Results: We demonstrated an absolute concordance in terms of specificity between the two methods, DD‐PCR showing a higher sensitivity (half a log higher than qPCR). As expected, a progressive increase of mutant allele burden was observed from essential thrombocythemia (ET) to polycythemia vera (PV) and primary myelofibrosis (PMF) to secondary myelofibrosis (SMF). Conclusion: In conclusion, our study showed that DD‐PCR could represent a new and promising technological evolution for detection of JAK2 mutation in MPNs.